Metal-loaded catalyst, electrode, and battery

JP2023129138A5Active Publication Date: 2025-02-28NISSHINBO IND INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022033944
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-02-28
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Conventional metal-supported catalysts face challenges in achieving both excellent durability and catalytic function simultaneously.

Method used

A metal-supported catalyst is developed with specific structural and compositional parameters, including a carbon support, noble metal particles, and defined Raman shift, pore sizes, and surface area ratios, enhancing both durability and catalytic performance.

Benefits of technology

The catalyst exhibits improved durability and catalytic function, suitable for applications in fuel cells and batteries, with enhanced stability and performance characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023129138000001
    Figure 2023129138000001
  • Figure 2023129138000002
    Figure 2023129138000002
  • Figure 2023129138000003
    Figure 2023129138000003
Patent Text Reader

Abstract

To provide a metal-loaded catalyst that exhibits both an excellent durability and an excellent catalytic function and also provide an electrode and a battery.SOLUTION: A metal-loaded catalyst comprises a carbon support and noble metal-containing catalyst metal particles supported by the carbon support. In the Raman spectrum provided by Raman spectroscopy, the half width at half maximum of the D band having a peak top in the vicinity of a Raman shift of 1340 cm-1 is at most 50.0 cm-1. The proportion of carbon anchoring is at least 15.0%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a metal-supported catalyst, an electrode, and a battery. [Background technology]

[0002] Patent Document 1 describes a catalyst comprising a support having micropores and catalyst particles, wherein the support contains carbon and at least a portion of the catalyst particles are embedded in the support.

[0003] Patent Document 2 describes a catalyst comprising a catalyst support and a catalyst metal supported on the catalyst support, wherein the BET specific surface area per unit weight of the support is 1200 m². 2 A catalyst is described that is characterized by having a charge of more than 0.7 mmol / g of support and a charge of 0.7 mmol / g or more of acidic groups per unit weight of support.

[0004] Patent Document 3 describes a catalyst particle and a carbon film covering the surface of the catalyst particle, wherein the chloride ion content per unit surface area of ​​the catalyst particle is 12.5 μg / m². 2 Electrode catalysts that are less than [amount missing] are listed. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2008-207072 [Patent Document 2] International Public Gazette No. 2014 / 175099 [Patent Document 3] Japanese Patent Publication No. 2020-136109 [Overview of the project] [Problems that the invention aims to solve]

[0006] However, conventionally, it has been difficult to realize metal-supported catalysts that combine excellent durability and superior catalytic function.

[0007] The present invention has been made in view of the above problems, and one of its objectives is to provide a metal-supported catalyst, an electrode, and a battery that have excellent durability and an excellent catalytic function.

Means for Solving the Problems

[0008] A metal-supported catalyst according to an embodiment of the present invention for solving the above problems is a metal-supported catalyst including a carbon carrier and catalyst metal particles containing a noble metal supported on the carbon carrier, and in a Raman spectrum obtained by Raman spectroscopy, the half-width at half-maximum of the D band having a peak top around a Raman shift of 1340 cm -1 is 50.0 cm or less, and the carbon anchoring ratio calculated by the following formula (I) is 15.0% or more. According to the present invention, a metal-supported catalyst having excellent durability and an excellent catalytic function is provided. -1 JPEG2023129138000001.jpg21170 (In the following formula (I), "electrochemically effective specific surface area" and "geometric specific surface area" are the electrochemically effective specific surface area (m / g-noble metal) and geometric specific surface area (m 2 / g-noble metal) of the noble metal contained in the metal-supported catalyst, respectively.) 2

[0009] The metal-supported catalyst may have an average pore diameter of 8.0 nm or less. Also, the metal-supported catalyst may have a ratio of the pore volume (cm 3 / g-carbon carrier) of pores with a pore diameter of 5 nm or more and 70 nm or less to the pore volume (cm 3 / g-carbon carrier) of pores with a pore diameter of less than 5 nm of 1.5 or more. Also, the metal-supported catalyst may have a BET specific surface area of 350 (m 2 / g-carbon carrier) or more. <>

[0010] Also, the metal-supported catalyst may have a ratio of the weight of the noble metal to the weight of the metal-supported catalyst of 30% by weight or more. Also, the metal-supported catalyst may have an electrochemically effective specific surface area of the noble metal of 45 (m​2 The metal-supported catalyst may also have a geometric specific surface area of ​​the precious metal of 52 (m²). 2 It may also be specified that the amount be greater than or equal to ( / g - precious metals).

[0011] Furthermore, the metal-supported catalyst has a carbon anchoring amount of 5.0 m³ calculated by the following formula (II). 2 It may also be specified that the value be 1 / g or more. JPEG2023129138000002.jpg28170 (In the above formula (II), "precious metal content (weight %)" is the ratio of the weight of the precious metal to the weight of the metal-supported catalyst, and "geometric specific surface area" and "electrochemical effective specific surface area" are the geometric specific surface area (m²) of the precious metal contained in the metal-supported catalyst, respectively. 2 (g - precious metals) and electrochemically effective specific surface area (m²) 2 (It is a precious metal.)

[0012] Furthermore, the metal-supported catalyst may have a durability index of 0.50 cm or more, calculated using the following formula (III). JPEG2023129138000003.jpg21170 (In the above formula (III), "carbon anchoring ratio (%)" is calculated by formula (I), and "Raman D half width at half maximum" is the half width at half maximum (cm) of the D band. -1 ) is. )

[0013] An electrode according to one embodiment of the present invention for solving the above problems includes any of the above-mentioned metal-supported catalysts. According to the present invention, an electrode having excellent properties is provided.

[0014] A battery according to one embodiment of the present invention for solving the above problems includes the electrodes. According to the present invention, a battery having excellent characteristics is provided. [Effects of the Invention]

[0015] According to the present invention, a metal-supported catalyst, electrode, and battery are provided that combine excellent durability and excellent catalytic function. [Brief explanation of the drawing]

[0016] [Figure 1] This diagram illustrates an example of the results of analyzing the Raman spectrum obtained by Raman spectroscopy of a metal-supported catalyst in an embodiment of this theory. [Figure 2A] This is an explanatory diagram showing an example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this product. [Figure 2B] This is an explanatory diagram showing another example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this present invention. [Figure 3] This is an explanatory diagram showing an example of the results of analyzing the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst in the embodiment of this product. [Figure 4A] This diagram illustrates the manufacturing conditions for the metal-supported catalyst and the results of evaluating the characteristics of the fuel cell containing the metal-supported catalyst in an embodiment of this model. [Figure 4B] This is an explanatory diagram showing the results of evaluating the properties of the metal-supported catalyst in the embodiment of this theory. [Modes for carrying out the invention]

[0017] One embodiment of the present invention is described below. However, the present invention is not limited to the examples shown in this embodiment.

[0018] The metal-supported catalyst according to this embodiment (hereinafter referred to as "the catalyst") comprises a carbon support and catalyst metal particles containing a noble metal supported on the carbon support.

[0019] The carbon support contained in this catalyst is a carbon material mainly composed of carbon. The carbon content of the carbon support may be, for example, 70% by weight or more, preferably 75% by weight or more, more preferably 80% by weight or more, and particularly preferably 85% by weight or more.

[0020] Furthermore, the carbon content of the carbon carrier may be, for example, 100% by weight or less, 95% by weight or less, or 90% by weight or less. The carbon content of the carbon carrier may be determined by any combination of the lower limit and the upper limit mentioned above. The carbon content of the carbon carrier is obtained by elemental analysis (combustion method).

[0021] The carbon carrier is preferably a carbonization material. The carbonization material is obtained by carbonizing a raw material containing organic matter. The organic matter content in the carbonization raw material may be, for example, 5% by weight or more and 90% by weight or less, and preferably 10% by weight or more and 80% by weight or less.

[0022] The organic matter contained in the raw materials is not particularly limited as long as it can be carbonized. Even if the organic compound is a polymer (e.g., thermosetting resins and / or thermoplastic resins) It is fine, and / or it may be an organic compound with a smaller molecular weight.

[0023] The carbon support preferably contains nitrogen. That is, the carbon support preferably contains nitrogen atoms in its carbon structure. The nitrogen-containing carbon support is preferably a nitrogen-containing carbonization material. The nitrogen-containing carbonization material can be obtained, for example, by carbonizing a raw material containing nitrogen-containing organic matter. The nitrogen-containing organic matter preferably contains nitrogen-containing organic compounds. The nitrogen-containing organic compound is not particularly limited as long as it is an organic compound that contains nitrogen atoms in its molecule. Furthermore, the nitrogen contained in the carbon support may be introduced by nitrogen doping treatment.

[0024] The nitrogen content of the carbon carrier may be, for example, 0.10% by weight or more, preferably 0.15% by weight or more, more preferably 0.20% by weight or more, even more preferably 0.25% by weight or more, and particularly preferably 0.30% by weight or more. The nitrogen content of the carbon carrier may also be, for example, 10.00% by weight or less. The nitrogen content of the carbon carrier is obtained by elemental analysis (combustion method) of the carbon carrier.

[0025] The carbon carrier is preferably a carbonized material obtained by carbonizing raw materials containing organic matter and metals. In this case, the carbon carrier may be a carbonized material that has undergone a metal removal treatment after carbonization. The metal removal treatment is a treatment that reduces the amount of metal derived from the raw materials contained in the carbonized material. Specifically, the metal removal treatment is preferably, for example, an acidic washing treatment and / or an electrolytic treatment.

[0026] If the carbon carrier is a carbonized material obtained by carbonizing raw materials containing organic matter and metal, the carbon carrier may contain metal derived from the raw materials used in the carbonization (hereinafter referred to as "raw material metal"). In this case, the carbon carrier contains the raw material metal inside the framework that constitutes its porous structure. Even if the carbon carrier is a carbonized material produced through a metal removal treatment as described above, raw material metal remains inside the framework of the carbon carrier. Of the raw material metal contained in the carbon carrier, the weight of the raw material metal contained inside the framework of the carbon carrier may be greater than the weight of the raw material metal contained on the surface of the framework of the carbon carrier.

[0027] The raw metal inside the carbon carrier's framework can be detected, for example, by performing a surface etching treatment on the framework and analyzing the cross-section exposed by the etching treatment. In other words, in this case, if one particle of the carbon carrier is etched, the raw metal can be detected in the cross-section of that particle exposed by the etching treatment. The raw metal contained in the carbon carrier can also be detected, for example, by inductively coupled plasma emission spectroscopy of the carbon carrier.

[0028] The raw material metal content of the carbon carrier (the ratio of the weight of the raw material metal contained in the carbon carrier to the weight of the carbon carrier) may be, for example, 0.001% by weight or more, 0.005% by weight or more, 0.01% by weight or more, or 0.02% by weight or more. Furthermore, the raw material metal content of the carbon carrier may be, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, or 0.5% by weight or less. The raw material metal content of the carbon carrier may be determined by any combination of the lower limit and the upper limit mentioned above. The raw material metal content of the carbon carrier can be obtained, for example, by inductively coupled plasma emission spectroscopy of the carbon carrier.

[0029] The raw material metal is preferably a transition metal. Specifically, the raw material metal is preferably a transition metal belonging to groups 3 to 12 of the periodic table, and is particularly preferably a transition metal belonging to the fourth period of groups 3 to 12 of the periodic table.

[0030] The raw material metal may be a transition metal other than platinum. Furthermore, the raw material metal may be a transition metal other than noble metals (e.g., ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au)).

[0031] Specifically, the raw material metal may be one or more selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), lanthanides (e.g., gadolinium (Gd)), and actinides. Preferably, it is one or more selected from the group consisting of Fe, Co, Ni, Cu, and Zn. More preferably, it is one or more selected from the group consisting of Fe, Co, Ni, and Zn. Particularly preferably, it is one or more selected from the group consisting of Co, Ni, and Zn.

[0032] Carbonization in the production of carbonized materials is carried out by heating the raw material to a temperature at which the organic matter contained in the raw material is carbonized. The carbonization temperature is not particularly limited as long as it is the temperature at which the raw material is carbonized, but for example, it is preferably 1200°C or higher, more preferably 1300°C or higher, even more preferably 1400°C or higher, and particularly preferably 1500°C or higher.

[0033] Furthermore, the carbonization temperature may be, for example, 3000°C or lower, preferably 2500°C or lower, and particularly preferably 2000°C or lower. The carbonization temperature may be determined by any combination of the lower limit and the upper limit mentioned above. The heating rate to the carbonization temperature is not particularly limited and may be, for example, 0.5°C / min or more and 300°C / min or less. Carbonization is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.

[0034] Carbonization may be carried out under normal pressure (atmospheric pressure), but it is preferable to carry it out under pressurized pressure (at a pressure greater than atmospheric pressure). When carbonization is carried out under pressurized pressure, the pressure of the atmosphere in which carbonization is carried out may be, for example, 0.05 MPa or higher in gauge pressure, preferably 0.15 MPa or higher, more preferably 0.20 MPa or higher, even more preferably 0.40 MPa or higher, and particularly preferably 0.50 MPa or higher. There is no particular upper limit to the pressure of the atmosphere in which carbonization is carried out, but the pressure may be, for example, 10 MPa or less in gauge pressure.

[0035] The carbon carrier is preferably a carbonized material that has been subjected to graphitization treatment after carbonization. That is, the carbon carrier is preferably a carbonized material obtained by, for example, subjecting a carbonized material obtained by carbonizing a raw material containing organic matter to graphitization treatment.

[0036] The graphitization treatment is carried out by heating the carbonization material at a temperature at which graphitization progresses. The heating temperature for heating the carbonization material in the graphitization treatment is not particularly limited as long as it is a temperature at which graphitization progresses in the carbonization material, but it is preferable that it is a higher temperature than the carbonization temperature required to obtain the carbonization material.

[0037] Specifically, the heating temperature in the graphitization treatment may be, for example, 1300°C or higher, preferably 1400°C or higher, more preferably 1500°C or higher, even more preferably 1600°C or higher, even more preferably 1700°C or higher, even more preferably 1750°C or higher, and particularly preferably 1800°C or higher.

[0038] Furthermore, the heating temperature in the graphitization treatment may be, for example, 3000°C or less, preferably 2500°C or less, more preferably 2400°C or less, even more preferably 2300°C or less, even more preferably 2250°C or less, even more preferably 2200°C or less, even more preferably 2150°C or less, and particularly preferably 2100°C or less. The heating temperature in the graphitization treatment may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above. The rate of heating up to the heating temperature in the graphitization treatment is not particularly limited and may be, for example, 0.5°C / min or more and 300°C / min or less. The graphitization treatment is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.

[0039] When the carbon carrier is a carbonized material that has been subjected to graphitization treatment after carbonization, it is preferable not to subject the carbonized material after graphitization treatment to pulverization treatment. That is, in the production of the carbon carrier, for example, it is preferable to adjust the median diameter by subjecting the carbonized material obtained by carbonization of the raw material to pulverization treatment, and then subject the pulverized carbonized material to graphitization treatment, and not subject the carbonized material after graphitization treatment to pulverization treatment.

[0040] The carbon support is preferably a carbon material that exhibits catalytic activity. In other words, in this case, the carbon support is a carbon catalyst that exhibits catalytic activity on its own. The carbon support, which is a carbon catalyst, is preferably a carbonized material obtained by carbonizing a raw material containing organic matter and metal, as described above.

[0041] The catalytic activity exhibited by the carbon support is preferably, for example, reducing activity and / or oxidizing activity, more preferably oxygen reducing activity and / or hydrogen oxidizing activity, and particularly preferably at least oxygen reducing activity.

[0042] In this catalyst, the catalyst metal particles supported on the carbon support contain noble metals. The catalyst metal particles containing noble metals include noble metals that do not form an alloy (hereinafter sometimes referred to as "pure noble metals") and / or noble metal alloys. A noble metal alloy is an alloy of a noble metal and a metal other than a noble metal (hereinafter referred to as "non-noble metal"). That is, a noble metal alloy contains one or more noble metals and one or more non-noble metals.

[0043] The precious metal is preferably one or more selected from the group consisting of ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au), more preferably one or more selected from the group consisting of Ru, Pd, Rh, Ir, and Pt, and particularly preferably Pt.

[0044] In other words, the catalyst metal particles preferably contain platinum. The catalyst metal particles containing platinum include platinum that does not form an alloy (hereinafter sometimes referred to as "pure platinum") and / or a platinum alloy. A platinum alloy is an alloy of platinum and a non-precious metal. In other words, a platinum alloy contains platinum and one or more non-precious metals. Furthermore, a platinum alloy may contain one or more other precious metals, or it may not contain any other precious metals.

[0045] The non-precious metals constituting the precious metal alloy are not particularly limited as long as they are metals other than precious metals that form an alloy with the precious metal, but are preferably transition metals other than precious metals. Specifically, the non-precious metals included in the precious metal alloy are preferably one or more selected from the group consisting of titanium (Ti), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), niobium (Nb), and cerium (Ce), more preferably one or more selected from the group consisting of Fe, Co, and Ni, and particularly preferably one or more selected from the group consisting of Co and Ni.

[0046] When the carbon carrier is a carbonization material for raw materials containing organic matter and raw material metals, the catalyst metal particles supported on the carbon carrier may contain the same type of metal as the raw material metal, or they may not contain the same type of metal as the raw material metal.

[0047] The catalytic activity of the catalytic metal particles is not particularly limited as long as the effects of the present invention are obtained, but it is preferable that the catalytic metal particles exhibit reducing activity and / or oxidizing activity, more preferably that they exhibit oxygen reducing activity and / or hydrogen oxidizing activity, and particularly preferably that they exhibit at least oxygen reducing activity.

[0048] This catalyst exhibits a Raman shift of 1340 cm⁻¹ in the Raman spectrum obtained by Raman spectroscopy. -1 Nearby (specifically, for example, 1320cm) -1 Above, 1360cm -1 The half-width at half maximum (hereinafter referred to as "Raman D half-width at half maximum") of the D-band with a peak top within the following range is 50.0 cm. -1 It is preferable to have a carbon structure that is as follows:

[0049] The Raman D half-width of this catalyst is, for example, 48.0 cm². -1 It is more preferable that the following conditions be met: 46.0 cm -1 It is even more preferable that the following conditions apply: 44.0 cm -1 It is even more preferable that the following conditions apply: 42.0 cm -1 It is even more preferable that the following conditions apply: 40.0 cm -1 It is even more preferable that the following conditions apply: 38.0 cm -1 Preferably, it is 36.0 cm. -1 It is more preferable that the following be the case: 34.0 cm -1 It is even more preferable that the following conditions apply: 32.0 cm -1 It is even more preferable that the following conditions apply: 30.0 cm -1 It is even more preferable that the following conditions apply: 28.0 cm -1 It is even more preferable that the following conditions apply: 26.0 cm -1 It is even more preferable that the following conditions apply: 25.0 cm -1The following is particularly preferable:

[0050] Furthermore, the Raman D half-width of the carbon structure of this catalyst is, for example, 20.0 cm. -1 It may be greater than or equal to 21.0 cm. -1 Preferably, it should be 22.0 cm or more. -1 It is more preferable that the length be greater than or equal to 22.5 cm. -1 The above is particularly preferable. The Raman D half-width of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0051] According to the reference (A. Sadezky et al., Carbon 43 (2005) 1731-1742), in the Raman spectrum of carbon materials, the D band represents components derived from carbon atoms close to disordered lattices, such as the edges of graphene layers. The half-width at half maximum (FMAX) of the D band indicates the crystallinity of carbon around the edges. That is, as the crystallinity of carbon around the edges in a carbon structure increases, the Raman D FMAX of that carbon structure decreases. Therefore, carbon structures exhibiting a Raman D FMAX below the upper limit mentioned above contain highly crystalline carbon around the edges, thus contributing to improved durability.

[0052] On the other hand, carbon structures exhibiting a Raman D half-width that is too small have excessively high crystallinity of carbon around the edges, making them unsuitable for supporting catalyst metal particles. In contrast, carbon structures exhibiting a Raman D half-width above the lower limit mentioned above contain carbon with appropriate crystallinity around the edges, resulting in excellent suitability for supporting catalyst metal particles and, consequently, contributing to improved durability and / or catalytic function of the metal-supported catalyst.

[0053] This catalyst has a BET specific surface area of ​​350 (m²). 2 It is preferable that the value is 1 / g-carbon support or higher. In this specification, the numerical unit " / g-carbon support" indicates the value per gram of carbon support contained in this catalyst. On the other hand, the numerical unit " / g" indicates the value per gram of this catalyst.

[0054] The BET specific surface area of ​​this catalyst is, for example, 400 (m²). 2 It is more preferable that the amount is 450 (m²) or more (1 / g-carbon support), and more preferably 450 (m²). 2 It is even more preferable that the amount is 500 (m²) or more (1 / g-carbon support), and 500 (m²) 2 It is more preferable that the amount is 550 (m²) or more (1 / g-carbon support), and 2 It is more preferably 600 (m²) or more (g² - carbon support), 2 It is more preferable that the amount is 650 (m²) or more (g-carbon support). 2 It is more preferably 700 (m²) or more (g² - carbon support), and 2 It is more preferably 750(m²) or more (1 / g-carbon support), 2 It is even more preferable that the value be 800 (m²) or more (1 / g-carbon support), and 800 (m²). 2 It is even more preferable that the amount is 850 (m²) or more (1 / g-carbon support), and 2 It is even more preferable that the value be 900 (m²) or more (1 / g-carbon support). 2 It is even more preferable that the carbon support ( / g) is 950(m 2 It is more preferably 1000 (m²) or more (1000 (m²) or more (1000 (m²)). 2 It is more preferably 1050(m²) or more (1g-carbon support). 2 It is even more preferable that the value be 1100 (m²) or more (1g-carbon support). 2 It is even more preferable that the amount is 1150 (m²) or more (1g-carbon support). 2 It is even more preferable that the value be 1200 (m²) or more (). 2 It is even more preferable that the amount is 1250 (m²) or more (1 / g-carbon support), and 2 It is even more preferable that the value be 1300 (m²) or more (1g-carbon support). 2 It is particularly preferable that the BET specific surface area of ​​this catalyst is 3000 (m²). 2 / g-carbon support) may be less than or equal to 2500(m 2 / g-carbon support) may be less than or equal to 2000(m 2 / g-carbon support) may be less than or equal to 1800(m 2 / g-carbon support) may be less than or equal to 1700(m 2 / g-carbon support) may be less than or equal to 1600(m 2 / g-carbon support) may be less than or equal to 1500(m 2 / g-carbon support) may be less than or equal to 1400(m 2 The BET specific surface area of ​​this catalyst may be less than or equal to ( / g-carbon support). The BET specific surface area of ​​this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0055] BET specific surface area (m²) of this catalyst 2 The BET specific surface area (m²) of this catalyst is obtained by the BET method from the nitrogen adsorption isotherm at a temperature of 77K (g-carbon support). 2 It is calculated from the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy ( / g) and the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy.

[0056] The catalyst preferably has an average pore diameter of 8.0 nm or less. In this case, the average pore diameter of the catalyst is more preferably 7.0 nm or less, even more preferably 6.0 nm or less, even more preferably 5.0 nm or less, even more preferably 4.5 nm or less, even more preferably 4.0 nm or less, even more preferably 3.8 nm or less, even more preferably 3.6 nm or less, even more preferably 3.4 nm or less, even more preferably 3.2 nm or less, even more preferably 3.0 nm or less, even more preferably 2.9 nm or less, even more preferably 2.8 nm or less, even more preferably 2.7 nm or less, even more preferably 2.6 nm or less, and especially preferably 2.5 nm or less.

[0057] Furthermore, the average pore diameter of this catalyst may be, for example, 1.0 nm or more, preferably 1.2 nm or more, more preferably 1.4 nm or more, even more preferably 1.6 nm or more, and particularly preferably 1.8 nm or more. The average pore diameter of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The average pore diameter of this catalyst is obtained from the nitrogen adsorption isotherm of the catalyst at a temperature of 77 K by the BJH method.

[0058] If the average pore size of a metal-supported catalyst is too large, for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, ionomers can easily enter the pores of the metal-supported catalyst. As a result, the catalyst metal particles supported in the pores become coated with ionomers, which can easily lead to a decrease in catalytic activity. In contrast, a porous structure with an average pore size below the upper limit mentioned above makes it difficult for ionomers to enter the pores, thus contributing to improved durability and / or catalytic function.

[0059] Furthermore, if the average pore size of the metal-supported catalyst is too small, the catalyst metal particles are more likely to be supported on the outer surface of the carbon support than within the pores, resulting in lower durability. In contrast, a porous structure with an average pore size above the lower limit mentioned above allows the catalyst metal particles to be effectively supported within the pores, thus contributing to improved durability.

[0060] This catalyst has a pore volume of pores with a diameter of 5 nm or more and 70 nm or less (hereinafter referred to as "5-70 nm pore volume") (cm²). 3 The volume of pores with a diameter of less than 5 nm relative to the g-carbon support (hereinafter referred to as "pore volume of less than 5 nm") (cm²) 3 It is preferable that the ratio of (g-carbon support) (hereinafter referred to as "less than 5 nm / 5-70 pore volume ratio") is 1.5 or higher.

[0061] The pore size ratio of less than 5 nm to 5-70 pores of this catalyst is more preferably 2.0 or higher, even more preferably 3.0 or higher, even more preferably 4.0 or higher, even more preferably 5.0 or higher, even more preferably 6.0 or higher, even more preferably 7.0 or higher, even more preferably 8.0 or higher, even more preferably 9.0 or higher, even more preferably 10.0 or higher, even more preferably 11.0 or higher, even more preferably 12.0 or higher, even more preferably 13.0 or higher, even more preferably 14.0 or higher, even more preferably 15.0 or higher, even more preferably 16.0 or higher, even more preferably 17.0 or higher, even more preferably 18.0 or higher, even more preferably 19.0 or higher, and particularly preferably 20.0 or higher.

[0062] Furthermore, the pore size ratio of less than 5 nm to 5-70 pore volume of this catalyst may be, for example, 50.0 or less, preferably 45.0 or less, more preferably 40.0 or less, even more preferably 35.0 or less, even more preferably 30.0 or less, even more preferably 25.0 or less, and particularly preferably 23.0 or less. The pore size ratio of less than 5 nm to 5-70 pore volume of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0063] The pore volume (cm³) of 5-70 nm used to calculate the pore volume ratio of less than 5 nm / 5-70 nm of this catalyst. 3 (g-carbon support) and pore volume (cm³) less than 5 nm 3 The pore volume (cm³) of this catalyst, obtained by the BJH method from nitrogen adsorption isotherms at a temperature of 77K, is 5-70 nm. 3 ( / g) and pore volume (cm³) of less than 5 nm 3 It is calculated from the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy ( / g) and the weight ratio of carbon supports contained in the catalyst obtained by inductively coupled plasma atomic emission spectroscopy.

[0064] If the pore volume ratio of less than 5 nm to 5-70 nm of a metal-supported catalyst is too small (i.e., the pore volume of 5-70 nm is too large compared to the pore volume of less than 5 nm), for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, the water generated can easily enter the pores, resulting in degradation due to oxidation of the catalyst metal particles supported within those pores. In contrast, a porous structure having a pore volume ratio of less than 5 nm to 5-70 nm above the lower limit mentioned above is less prone to degradation of the catalyst metal particles supported within the pores, thus contributing to improved durability and / or functionality of the metal-supported catalyst.

[0065] Furthermore, if the pore volume ratio of less than 5 nm to 5-70 nm of a metal-supported catalyst is too large (i.e., the pore volume of less than 5 nm is too large compared to the pore volume of 5-70 nm), then, for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, the diffusivity of the material within the pores is low, which tends to degrade the power characteristics. In contrast, a porous structure having a pore volume ratio of less than 5 nm to 5-70 nm below the upper limit mentioned above improves the diffusivity of the material, thus contributing to improved power characteristics.

[0066] The catalyst preferably has a precious metal content of 30% by weight or more. More specifically, the precious metal contained in the catalyst (more specifically, the precious metal contained in the catalyst metal particles) is the ratio of the weight of the catalyst to the total weight of the catalyst (hereinafter referred to as "precious metal content"). The precious metal content of the catalyst is more preferably 35% by weight or more, even more preferably 40% by weight or more, even more preferably 45% by weight or more, and particularly preferably 50% by weight or more. Furthermore, the precious metal content of the catalyst may be, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less. The precious metal content of the catalyst may be determined by any combination of the lower limit and the upper limit mentioned above. The precious metal content of the catalyst is obtained by inductively coupled plasma atomic emission spectroscopy.

[0067] This catalyst has an electrochemical effective specific surface area (ECSA) of 45 (m²) of the noble metal contained in the catalyst metal particles. 2It is preferable that the value is 1 / g-precious metal or higher. The numerical unit "1 / g-precious metal" indicates the value per gram of precious metal contained in this catalyst.

[0068] The ECSA of the precious metal contained in this catalyst is, for example, 50 (m 2 It is more preferable that it be 55 (m) or more (g - precious metals). 2 It is even more preferable that the amount is 60 (m) or more (g - precious metals). 2 It is more preferable that the amount is 65 (m) or more (g - precious metals). 2 It is even more preferable that it be 70 (m) or more (g - precious metals). 2 It is more preferable that the amount is 75 (m) or more (g - precious metals). 2 It is even more preferable that the amount is 80 (m) or more (g - precious metals). 2 It is particularly preferable that the ECSA of the precious metal contained in this catalyst be 200 (m³). 2 / g - precious metals) may be less than or equal to 180(m 2 / g - precious metals) may be less than or equal to 160(m 2 / g - precious metals) may be less than or equal to 140(m 2 / g - precious metals) may be less than or equal to 120(m 2 / g - precious metals) may be less than or equal to 100(m 2 The ECSA of the precious metal contained in this catalyst may be less than or equal to / g-precious metal. The ECSA of the precious metal contained in this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0069] For example, if the precious metal contained in the catalyst metal particles supported on this catalyst is platinum, then the ECSA (m) of the precious metal contained in this catalyst is 2 / g-precious metals) is the ECSA (m) of platinum contained in this catalyst. 2 The value is ( / g-Pt). Here, the numerical unit " / g-Pt" indicates the value per gram of platinum contained in this catalyst.

[0070] The ECSA of the noble metal contained in this catalyst is obtained by cyclic voltammetry with a potential sweep at a sweep rate of 10 mV / sec using a rotating ring-disk electrode device having a working electrode on which this catalyst is supported.

[0071] This catalyst preferably has a geometric specific surface area of the noble metal contained in the catalyst metal particles of 52 (m 2 / g-noble metal) or more. The geometric specific surface area of the noble metal contained in this catalyst is, for example, more preferably 55 (m 2 / g-noble metal) or more, even more preferably 60 (m 2 / g-noble metal) or more, even more preferably 70 (m 2 / g-noble metal) or more, even more preferably 75 (m 2 / g-noble metal) or more, even more preferably 80 (m 2 / g-noble metal) or more, even more preferably 85 (m 2 / g-noble metal) or more, even more preferably 90 (m 2 / g-noble metal) or more, even more preferably 95 (m 2 / g-noble metal) or more, even more preferably 100 (m 2 / g-noble metal) or more, even more preferably 105 (m 2 / g-noble metal) or more, even more preferably 110 (m 2 / g-noble metal) or more, even more preferably 115 (m 2 / g-noble metal) or more, and particularly preferably 115 (m 2 The geometric specific surface area of the noble metal contained in this catalyst may, for example, also be 200 (m 2 / g-noble metal) or less, 190 (m 2 / g-noble metal) or less, 180 (m 2 / g-noble metal) or less, 170 (m 2 / g-noble metal) or less, 160 (m 2 / g-noble metal) or less, 150 (m 2 / g-noble metal) or less, 145 (m 2 / g-noble metal) or less. / g - precious metals) may be less than or equal to 135(m 2 / g - precious metals) may be less than or equal to 130(m 2 The geometric specific surface area (m²) of the precious metal contained in this catalyst may be less than or equal to / g. 2 The value of (g - precious metals) may be determined by any combination of the lower limit and the upper limit mentioned above.

[0072] Furthermore, if the precious metal contained in the catalyst metal particles supported on this catalyst is platinum, the geometric specific surface area (m²) of the precious metal contained in this catalyst is... 2 / g-precious metal) is the geometric specific surface area (m²) of platinum contained in this catalyst. 2 ( / g-Pt)

[0073] The geometric specific surface area of ​​the noble metal contained in this catalyst is obtained by powder X-ray diffraction of the catalyst. Specifically, the geometric specific surface area of ​​the noble metal contained in this catalyst is obtained by separating the peaks of the (111) diffraction line of the noble metal that appears in the X-ray diffraction pattern obtained by powder X-ray diffraction of the catalyst, calculating the value of "6 / density / crystallite diameter × peak area ratio × noble metal atom ratio" for each peak obtained by the peak separation, and summing up the calculated values ​​for all peaks.

[0074] This catalyst preferably has a carbon anchoring ratio of 15.0% or more, calculated by the following formula (I). JPEG2023129138000004.jpg21170

[0075] In the above formula (I), "electrochemical effective specific surface area" and "geometric specific surface area" are the electrochemical effective specific surface area (m²) of the noble metal contained in this catalyst, respectively. 2 (g - precious metals) and geometric specific surface area (m²) 2 (g - precious metals)

[0076] The carbon anchoring ratio of this catalyst is more preferably 16.0% or more, more preferably 18.0% or more, even more preferably 20.0% or more, even more preferably 21.0% or more, even more preferably 22.0% or more, even more preferably 23.0% or more, even more preferably 24.0% or more, even more preferably 25.0% or more, even more preferably 26.0% or more, even more preferably 27.0% or more, and particularly preferably 28.0% or more.

[0077] Furthermore, the carbon anchoring ratio of this catalyst may be, for example, 50.0% or less, 45.0% or less, 40.0% or less, 35.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, or 30.0% or less. The carbon anchoring ratio of this catalyst may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0078] For example, if the catalyst metal particles supported on the carbon support in this catalyst include platinum as a precious metal, the carbon anchoring ratio of this catalyst is expressed in formula (I) above as follows: "electrochemical effective specific surface area" and "geometric specific surface area" are respectively the electrochemical effective specific surface area (m²) of the platinum contained in this catalyst. 2 ( / g - Pt) and geometric specific surface area (m²) 2 It is calculated using ( / g - Pt).

[0079] The carbon anchoring ratio (%) represents the proportion of the geometric specific surface area of ​​the noble metal (e.g., platinum) contained in the catalyst metal particles supported on the carbon support that does not contribute to the electrochemical effective specific surface area (ECSA) of the noble metal. Therefore, the carbon anchoring ratio (%) reflects the proportion of the surface area of ​​the catalyst metal particles supported on the carbon support that is coated with carbon (specifically, the surface area of ​​the portion that is firmly fixed (anchored) to the carbon support by being coated with carbon). Consequently, in metal-supported catalysts having a carbon anchoring ratio above the lower limit mentioned above, a portion of the catalyst metal particles is effectively fixed to the carbon support, and thus the metal-supported catalyst exhibits excellent durability and / or catalytic function.

[0080] On the other hand, an excessively large carbon anchoring ratio indicates that the ratio of the carbon-coated surface area to the surface area of ​​the catalyst metal particles supported on the carbon carrier is too large, meaning that the ratio of the surface area contributing to the catalytic function to the surface area of ​​the catalyst metal particles is too small. Therefore, if the carbon anchoring ratio of a metal-supported catalyst is too large, for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, the power characteristics tend to deteriorate. In contrast, a carbon anchoring ratio below the upper limit mentioned above indicates that the catalytic surface area of ​​the catalyst metal particles coated on the carbon carrier is large, contributing to improved power characteristics.

[0081] This catalyst has a carbon anchoring amount of 5.0 m³ calculated by the following formula (II). 2 It is preferable that the amount is 1 / g or more. JPEG2023129138000005.jpg28170

[0082] In equation (II) above, "precious metal content (weight %)" is the ratio (weight %) of the weight of the precious metal contained in the catalyst to the total weight of the catalyst, and is obtained by inductively coupled plasma atomic emission spectroscopy. Furthermore, "geometric specific surface area" and "electrochemical effective specific surface area" are the geometric specific surface area (m²) of the precious metal contained in the catalyst, respectively. 2 (g - precious metals) and electrochemically effective specific surface area (m²)2 (g - precious metals)

[0083] The carbon anchoring amount of this catalyst is, for example, 6.0 m 2 It is more preferable that the amount be 7.0m or more. 2 It is even more preferable that it be 8.0m or more per gram. 2 It is even more preferable that it be 9.0m or more per gram. 2 It is even more preferable that it be 10.0m or more per gram. 2 It is even more preferable that it be 11.0m or more per gram. 2 It is even more preferable that it be 12.0m or more per g. 2 It is even more preferable that it be 13.0m or more per gram. 2 It is even more preferable that it be 14.0m or more per gram. 2 It is even more preferable that it be 15.0m or more per gram. 2 It is particularly preferable that the amount be 1 / g or more.

[0084] Furthermore, the carbon anchoring amount of this catalyst is, for example, 40.0 m 2 It may be less than / g, and 35.0m 2 It is preferable that the amount be less than or equal to 30.0m 2 It is more preferable that the amount be less than or equal to 25.0m 2 It is even more preferable that it be less than or equal to / g, and 20.0m 2 It is particularly preferable that the amount of carbon anchoring of this catalyst be less than or equal to / g. The amount of carbon anchoring of this catalyst may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0085] For example, if the catalyst metal particles supported on the carbon support in this catalyst contain platinum as a precious metal, the carbon anchoring amount of this catalyst is calculated in formula (II) above, where "precious metal content" is the "platinum content (weight %)", which is the ratio of the weight of platinum contained in this catalyst to the weight of this catalyst, and "electrochemical effective specific surface area" and "geometric specific surface area" are the electrochemical effective specific surface area (m²) of the platinum contained in this catalyst, respectively. 2 ( / g - Pt) and geometric specific surface area (m²) 2It is calculated using ( / g - Pt).

[0086] Carbon anchoring amount (m 2 The value (m² / g) is calculated considering the noble metal content (weight %) of the catalyst metal particles in the metal-supported catalyst, and represents the surface area (m²) of the carbon-coated noble metal contained in 1g of the metal-supported catalyst. 2 This parameter corresponds to ). Therefore, in metal-supported catalysts having a carbon anchoring amount greater than or equal to the lower limit mentioned above, a portion of the catalyst metal particles are effectively fixed to the carbon support, and thus the metal-supported catalyst exhibits excellent durability and / or catalytic function.

[0087] On the other hand, an excessively large amount of carbon anchoring indicates that the carbon-coated surface area of ​​the catalyst metal particles supported on the carbon carrier is too large, meaning that the surface area contributing to the catalytic function of the catalyst metal particles is too small. Therefore, if the amount of carbon anchoring of a metal-supported catalyst is too large, for example, when the metal-supported catalyst is used as an electrode catalyst in a fuel cell, the power characteristics tend to deteriorate. In contrast, a carbon anchoring amount below the upper limit mentioned above indicates that the catalytic surface area of ​​the catalyst metal particles coated on the carbon carrier is large, contributing to improved power characteristics.

[0088] The catalyst is preferably such that the durability index calculated by the following formula (III) is 0.50 cm or higher. JPEG2023129138000006.jpg21170

[0089] As mentioned above, the Raman D half-width at half maximum indicates the crystallinity of carbon around the edges in the carbon structure, and the higher the degree of carbon crystallinity, the smaller the value. Therefore, as an indicator of durability that takes into account the degree of carbon crystallinity, we use a durability index calculated by the product of the reciprocal of the Raman D half-width at half maximum and the carbon anchoring ratio.

[0090] The durability index of this catalyst is more preferably 0.55 cm or more, even more preferably 0.60 cm or more, even more preferably 0.65 cm or more, even more preferably 0.70 cm or more, even more preferably 0.75 cm or more, even more preferably 0.80 cm or more, even more preferably 0.85 cm or more, even more preferably 0.90 cm or more, even more preferably 0.95 cm or more, even more preferably 1.00 cm or more, even more preferably 1.05 cm or more, even more preferably 1.10 cm or more, and particularly preferably 1.15 cm or more. Furthermore, the durability index of this catalyst may be, for example, 5.00 cm or less, 4.50 cm or less, 4.00 cm or less, 3.50 cm or less, 3.00 cm or less, 2.50 cm or less, 2.00 cm or less, or 1.50 or less. The durability index of this catalyst may be determined by any combination of the lower limit and the upper limit mentioned above.

[0091] The method for producing a metal-supported catalyst according to this embodiment (hereinafter referred to as "this method") includes an impregnation step of impregnating a carbon support with a metal precursor constituting catalyst metal particles; a reduction treatment step of subjecting the metal precursor impregnated in the carbon support to a reduction treatment to obtain a metal-supported catalyst on which the metal particles are supported; and a heat treatment step of subjecting the metal-supported catalyst to a heat treatment.

[0092] In the impregnation process, the carbon carrier is impregnated with precursors of the metals that will constitute the catalyst metal particles. That is, for example, when supporting catalyst metal particles containing pure precious metals, the precursor of the said precious metal is impregnated into the carbon carrier. Also, when supporting catalyst metal particles containing a precious metal alloy, the precursors of the said precious metal and the precursors of the non-precious metals that will constitute the said precious metal alloy are impregnated into the carbon carrier.

[0093] In the reduction treatment step, the carbon carrier impregnated with a metal precursor in the impregnation step is subjected to a reduction treatment to obtain a metal-supported catalyst containing the carbon carrier and the metal particles supported on the carbon carrier. The reduction treatment may be a liquid-phase reduction treatment or a gas-phase reduction treatment, but a gas-phase reduction treatment is preferred.

[0094] In the heat treatment step, the metal-supported catalyst obtained in the reduction treatment step is subjected to a heat treatment in which a portion of the individual catalyst metal particles are coated with carbon contained in the carbon support of the metal-supported catalyst.

[0095] The atmosphere in which the heat treatment is performed is not particularly limited as long as the effects of the present invention are obtained, but it is preferable to perform the treatment in an atmosphere containing an inert gas (for example, one or more selected from the group consisting of nitrogen gas, argon gas, helium gas, and neon gas) or in a vacuum.

[0096] The concentration of the inert gas in the atmosphere used for heat treatment is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, even more preferably 80% by volume or more, even more preferably 90% by volume or more, and particularly preferably 100% by volume.

[0097] The temperature at which the metal-supported catalyst is heated during the heat treatment (heat treatment temperature) is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 600°C or higher, more preferably 650°C or higher, even more preferably 700°C or higher, even more preferably 750°C or higher, and particularly preferably 800°C or higher. The heat treatment temperature may also be, for example, 1300°C or lower, preferably 1100°C or lower, more preferably 1000°C or lower, and particularly preferably 900°C or lower. The heat treatment temperature may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0098] The time for heating the metal-supported catalyst at the heat treatment temperature (heat treatment time) is not particularly limited as long as the effects of the present invention are obtained, but for example, it is preferably 5 minutes or more, more preferably 10 minutes or more, even more preferably 20 minutes or more, even more preferably 30 minutes or more, even more preferably 40 minutes or more, even more preferably 60 minutes or more, even more preferably 80 minutes or more, and particularly preferably 100 minutes or more. Also, the heat treatment time may be, for example, 24 hours or less, preferably 12 hours or less, more preferably 6 hours or less, even more preferably 180 minutes or less, and particularly preferably 150 minutes or less. The heat treatment time may be determined by arbitrarily combining any of the lower limits and any of the upper limits mentioned above.

[0099] According to this method, a metal-supported catalyst possessing both excellent durability and superior catalytic function can be produced. In other words, the catalyst described above is preferably produced by this method.

[0100] The electrode according to this embodiment (hereinafter referred to as "the electrode") includes the catalyst. That is, the electrode is a battery electrode comprising, for example, an electrode substrate and the catalyst supported on the electrode substrate. The electrode is preferably a battery electrode. That is, the electrode is preferably an electrode for a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a water electrolytic cell (e.g., a polymer electrolyte water electrolytic cell), a redox flow battery, or a halogen battery.

[0101] This electrode may be a cathode or an anode, but it is preferably a cathode. That is, this electrode is the cathode or anode of a fuel cell, air battery, water electrolytic cell, redox flow battery, or halogen battery, and is preferably a cathode.

[0102] The battery according to this embodiment (hereinafter referred to as "the battery") includes the electrode. Specifically, the battery is preferably a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a redox flow battery, or a halogen battery that includes the electrode. The battery is preferably a membrane / electrode assembly (MEA) that includes the electrode.

[0103] This battery is a battery having this electrode as the cathode or anode, preferably a battery having this electrode as the cathode. That is, this battery is a fuel cell, air battery, redox flow battery, or halogen battery having this electrode as the cathode or anode, preferably a fuel cell, air battery, redox flow battery, or halogen battery having this electrode as the cathode.

[0104] Next, a specific example of this embodiment will be described. [Examples]

[0105] [Manufacturing of carbon carriers] 1.0 g of polyacrylonitrile (PAN), 1.0 g of 2-methylimidazole, 6.0 g of zinc chloride (ZnCl2), and 30 g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated in an air atmosphere and infusible at 250°C.

[0106] The mixture, after being rendered infusible, was carbonized by heating it at 1500°C under a nitrogen atmosphere and a gauge pressure of 0.90 MPa. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization and the mixture was stirred. Subsequently, the suspension containing the carbonized material was filtered using a filtration membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. Thus, metal removal treatment was performed by acid washing.

[0107] The carbonized material, after metal removal treatment, was pulverized using a fine grinder until the median particle size was 0.4 μm or less. The pulverized carbonized material was then vacuum-dried to remove moisture. Subsequently, the carbonized material was heat-treated at 300°C in a nitrogen atmosphere. The resulting carbonized material was used as the carbon carrier C1500.

[0108] Furthermore, the carbonized material obtained in the same manner as in the case of carbon carrier C1500 described above was used as carbon carrier C2000, except that 2000°C was used as the carbonization temperature instead of 1500°C.

[0109] Furthermore, the carbon carrier C1500 was subjected to graphitization treatment by heating it in a nitrogen atmosphere under atmospheric pressure at 1800°C, 2000°C, 2100°C, or 2400°C. The carbonized materials obtained by these graphitization treatments at 1800°C, 2000°C, 2100°C, and 2400°C were used as carbon carrier C1500-G1800, carbon carrier C1500-G2000, carbon carrier C1500-G2100, and carbon carrier C1500-G2400, respectively.

[0110] Commercially available Ketjenblack (EC600JD, manufactured by Lion Specialty Chemicals Co., Ltd.) was used as the carbon carrier KB. Furthermore, the carbon carrier KB was subjected to graphitization treatment by heating it at 2000°C under atmospheric pressure in a nitrogen atmosphere. The carbon material obtained by this graphitization treatment was used as the carbon carrier KB-G2000.

[0111] [Manufacturing of metal-supported catalysts] In Examples 1, 3-6, C2, C4, and C5, platinum particles were supported on a carbon carrier by the following gas-phase reduction method. First, an impregnation process was carried out. Specifically, 1 g of carbon carrier and 20 g of an aqueous solution containing chloroplatinic acid (H2PtCl6), a platinum precursor, in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 1 g), were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 66 hours. This impregnation process was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0112] Next, a reduction process was carried out. Specifically, the mixture obtained in the impregnation process was dried under vacuum at 100°C, and then maintained at 150°C in a nitrogen atmosphere to volatilize the solvent components. The resulting solid was then subjected to a heat treatment (gas-phase reduction treatment) at 350°C for 120 minutes in a hydrogen atmosphere (100% hydrogen gas by volume).

[0113] Subsequently, a heat treatment process was carried out. Specifically, the solid obtained in the reduction process was subjected to heat treatment at 825°C for 120 minutes in a nitrogen atmosphere. In this way, a metal-supported catalyst was obtained containing a carbon support (carbon support C1500 in Example 1, carbon support C1500-G1800 in Example 3, carbon support C1500-G2000 in Example 4, carbon support C1500-G2100 in Example 5, carbon support C2000 in Example 6, carbon support C1500-G2400 in Example C2, carbon support KB in Example C4, and carbon support KB-G2000 in Example C5) and platinum particles supported on the carbon support.

[0114] In Example 2, a metal-supported catalyst containing a carbon carrier C1500 and platinum particles supported on the carbon carrier was obtained in the same manner as in Example 1, except that in the impregnation process, the mixed solution was held under normal pressure for 2 hours instead of being held under vacuum and pressure, and in the heat treatment process, 40 minutes was used instead of 120 minutes for the heat treatment time.

[0115] In Example 7, a metal-supported catalyst containing a carbon carrier C1500-G2000 and platinum particles supported on the carbon carrier was obtained in the same manner as in Example 1 and other cases described above, except that 40 minutes was used instead of 120 minutes for the heat treatment process.

[0116] In Example 8, a metal-supported catalyst containing a carbon carrier C2000 and platinum particles supported on the carbon carrier was obtained in the same manner as in Example 1 and other cases described above, except that the mixed solution was held under normal pressure for 2 hours instead of being held under vacuum and pressure during the impregnation process.

[0117] In Example 9, platinum alloy particles were supported on a carbon carrier by the following gas-phase reduction method. First, the first impregnation step was performed. Specifically, 1 g of carbon carrier and 14 g of an aqueous solution containing chloroplatinic acid (H2PtCl6) in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 0.70 g) were stirred and mixed for 1 hour. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 66 hours. This first impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0118] Next, a first gas-phase reduction process was carried out. Specifically, the mixture obtained in the first impregnation process was dried under vacuum at 100°C, and then held at 150°C in a nitrogen atmosphere to volatilize the solvent components. The resulting solid was subjected to a heat treatment (first gas-phase reduction treatment) at 350°C for 120 minutes in a hydrogen atmosphere (100% hydrogen gas by volume) to obtain a platinum-supported catalyst.

[0119] Next, the second impregnation step was carried out. Specifically, 1.7 g of the platinum-supported catalyst obtained in the first gas-phase reduction step and 20 g of an aqueous solution containing cobalt chloride (CoCl2), a cobalt precursor, in an amount that resulted in a cobalt concentration of 0.21% by weight (cobalt content of 0.042 g) were stirred and mixed for 18 hours. The mixed solution was first held under reduced pressure of -0.10 MPa or less (specifically, -0.10 MPa to -0.1013 MPa) for 1 hour, then held under increased pressure of 0.15 MPa or more (specifically, 0.15 MPa to 0.20 MPa) for 1 hour, and then stirred and mixed for 18 hours. This second impregnation step was carried out while maintaining the temperature of the mixed solution at 5°C or less (specifically, 0°C to 5°C).

[0120] Next, the second gas-phase reduction process and the heat treatment process were carried out consecutively. Specifically, the mixture obtained in the second impregnation process was dried under vacuum at 100°C. The obtained solid was subjected to a heat treatment (second gas-phase reduction treatment) at 700°C for 60 minutes in a hydrogen atmosphere (100% hydrogen gas by volume), and then, while maintaining the atmosphere temperature within the range of 650 to 750°C, the hydrogen atmosphere was replaced with a nitrogen atmosphere (100% nitrogen gas by volume), and the solid was subjected to a heat treatment at 700°C for 120 minutes in the nitrogen atmosphere to obtain a platinum alloy-supported catalyst.

[0121] Next, a post-treatment process was carried out. Specifically, in order to remove excess metal from the platinum alloy-supported catalyst obtained in the heat treatment process, the platinum alloy-supported catalyst was mixed with a 10% nitric acid solution for 2 hours. After that, the platinum alloy-supported catalyst and the acid solution were separated by filtration, and the platinum alloy-supported catalyst was further washed with distilled water until the filtrate was neutral. The washed platinum alloy-supported catalyst was dried under vacuum at 60°C to remove moisture.

[0122] Subsequently, to remove nitric acid, the platinum alloy-supported catalyst was heat-treated at 300°C in a nitrogen atmosphere. Furthermore, to reduce and remove platinum oxide, the platinum alloy-supported catalyst was heat-treated at 700°C in a nitrogen atmosphere. In this way, a metal-supported catalyst containing a carbon support C1500-G1800 and platinum and cobalt alloy particles supported on the carbon support was obtained.

[0123] In Example C1, a metal-supported catalyst containing a carbon support C1500 and platinum particles supported on the carbon support was obtained in the same manner as in Example 1 and other cases described above, except that 600°C was used as the heat treatment temperature in the heat treatment step instead of 825°C.

[0124] In Example C3, platinum particles were supported on a carbon carrier by the following liquid-phase reduction method. First, an impregnation step was performed. Specifically, 1 g of carbon carrier and 22.2 g of an aqueous solution containing chloroplatinic acid (H2PtCl6) in an amount that resulted in a platinum concentration of 5% by weight (platinum content of 1.1 g) were stirred and mixed for 66 hours.

[0125] Next, a liquid-phase reduction process was carried out. Specifically, ethylene glycol was added as a reducing agent to the mixture obtained in the impregnation process, and the mixture was held at 80°C in an air atmosphere for 4 hours to perform a liquid-phase reduction treatment and obtain a platinum-supported catalyst. Subsequently, the obtained mixture was dried at 100°C under vacuum and then held at 150°C in a nitrogen atmosphere to volatilize the solvent components. In this way, a metal-supported catalyst containing carbon carrier C1500-G1800 and platinum particles supported on the carbon carrier was obtained.

[0126] In Example C6, a commercially available platinum-supported catalyst Pt / C-1, which includes a solid carbon support without pores and platinum particles supported on the carbon support, was used as the metal-supported catalyst.

[0127] In Example C7, a commercially available platinum-supported catalyst Pt / C-2, which contains Ketjenblack and platinum particles supported on the Ketjenblack, was used as the metal-supported catalyst.

[0128] [Raman spectroscopy] The metal-supported catalyst was analyzed by Raman spectroscopy. The Raman spectra were measured using the HORIBA micro-laser Raman spectroscopy system (LabRAM, HORIBA Jobin Yvon). The laser used for the measurement had an excitation wavelength of 532 nm, an output of 50 mW, and was measured through a light-reducing filter D3 under conditions of 90 seconds of exposure × 2 integrations to obtain the Raman spectra.

[0129] Baseline correction was applied to the obtained Raman spectra. That is, Raman shift (cm) -1 ) is 600cm -1 Scattering intensity in the vicinity and 2000 cm -1 A straight line connecting the scattering intensities of the vicinity was determined as the baseline, and baseline correction was performed by subtracting this baseline from each intensity in the scattering spectrum.

[0130] Next is the Raman shift, 1340cm -1 Nearby (specifically, 1320cm) -1 Above, 1360cm -1 We identified the D band with a peak top within the following range. Then, the intensity of the D band I d (Raman shift (cm) corresponding to the intensity of the peak top of the D band) -1 )A d Therefore, the intensity of the D band I d Raman shift (cm) corresponding to half the intensity -1 )B d By subtracting this, the Raman D half-width at half maximum (cm) -1 The Raman D half-width (cm) was calculated. Specifically, the Raman D half-width of the metal-supported catalyst was calculated using the following formula: Raman D half-width (cm) -1 )=A d (cm -1 )-B d (cm -1 ).

[0131] Here, Figure 1 shows an example of a Raman spectrum, specifically the result of analyzing the Raman spectrum obtained by Raman spectroscopy of the metal-supported catalyst in Example 1. In Figure 1, the horizontal axis represents the Raman shift (cm). -1 The vertical axis shows the scattering intensity after baseline correction, and A d This is the Raman shift (cm) corresponding to the peak top of the D band. -1 ) shows B d is A d D-band intensity I at lower wavenumbers d The Raman shift (cm) corresponds to the Raman spectrum showing half the intensity of the peak top of the D band. -1) indicates.

[0132] [Metal content: Inductively coupled plasma atomic emission spectroscopy] The platinum and non-platinum metal (metals other than platinum) content of the metal-supported catalyst was measured by inductively coupled plasma atomic emission spectroscopy (ICP-OES). Specifically, 100 mg of the metal-supported catalyst was first heated and held at 800°C in an air atmosphere for 3 hours to remove non-metallic components from the catalyst.

[0133] Next, the metal-supported catalyst was immersed in 5 mL of aqua regia and heated at 50°C for 1 hour to dissolve the metal contained in the catalyst. Furthermore, distilled water was added to dilute the solution to a volume of 50 mL to obtain a metal solution. Subsequently, the platinum concentration and non-platinum metal concentration of the obtained metal solution were measured using a sequential plasma emission spectrometer (ICPS-8100, manufactured by Shimadzu Corporation).

[0134] Then, by multiplying the platinum concentration (mg / mL) and non-platinum metal concentration (mg / mL) of the metal solution by the volume of the metal solution (50 mL), the platinum content (mg) and non-platinum metal content (mg) per 100 mg of metal-supported catalyst were obtained.

[0135] Furthermore, the platinum content (weight %) and non-platinum metal content (weight %) obtained by ICP-OES were calculated by dividing the weight of platinum (mg) and non-platinum metal (mg) contained in the metal-supported catalyst by the weight of the metal-supported catalyst, which is 100 mg, and then multiplying by 100. In addition, the sum of the platinum content (weight %) and non-platinum metal content (weight %) of the metal-supported catalyst was obtained as the metal content (weight %) of the metal-supported catalyst.

[0136] [Specific surface area, average pore diameter, and total pore volume] The specific surface area, average pore diameter, and total pore volume of metal-supported catalysts were measured using a specific surface area / pore distribution analyzer (TriStar II 3020, manufactured by Shimadzu Corporation) and its accompanying analysis software (TriStar II 3020).

[0137] In other words, first, 0.1 g of metal-supported catalyst is heated at 100°C, 6.7 × 10⁻⁶ -2 By holding the metal-supported catalyst at Pa for 3 hours, the water adsorbed on it was removed. Next, at a temperature of 77K, the change in the amount of nitrogen adsorbed onto the metal-supported catalyst in response to a change in nitrogen gas pressure was measured to obtain a nitrogen adsorption isotherm at 77K.

[0138] Then, using the nitrogen adsorption isotherm at a temperature of 77K, the BET specific surface area (m²) of the metal-supported catalyst by nitrogen adsorption was determined. 2 The BET specific surface area (m²) of the metal-supported catalyst was obtained. 2 Based on the BET specific surface area (m²) per gram of carbon support contained in the metal-supported catalyst, obtained by the above-mentioned ICP-OES, the BET specific surface area (m²) per gram of carbon support contained in the metal-supported catalyst is calculated. 2 The weight ratio of carbon support ( / g - carbon support) was calculated. Specifically, the weight ratio of carbon support contained in the metal-supported catalyst was first calculated using the following formula: Weight ratio of carbon support = 1 - (Metal content obtained by ICP-OES (weight %)) / 100. Next, the BET specific surface area (m²) of the metal-supported catalyst was calculated using the obtained weight ratio of carbon support. 2 By dividing by ( / g), the BET specific surface area (m²) per gram of carbon support can be calculated. 2 The amount of carbon support ( / g) was calculated.

[0139] Furthermore, using the BJH method, the volume of pores with a diameter of 5 nm or more and 70 nm or less (5-70 nm pore volume) (cm³) was obtained from the nitrogen adsorption isotherm at a temperature of 77 K. 3 (per g) and the volume of pores with a diameter of less than 5 nm (pore volume less than 5 nm) (cm³ 3 We obtained / g).

[0140] Furthermore, similar to the BET specific surface area described above, the pore volume of 5-70 nm (cm³) per gram of carbon support contained in the metal-supported catalyst is determined based on the metal content of the metal-supported catalyst obtained by ICP-OES. 3 (g-carbon support) and pore volume (cm³) less than 5 nm 3 The amount of carbon support ( / g) was calculated.

[0141] Furthermore, pore volume less than 5 nm (cm 3 (g-carbon support) 5-70 nm pore volume (cm 3 By dividing by (g-carbon support), the pore volume of 5-70 nm (cm³) is obtained. 3 / g-carbon support) and the pore volume less than 5 nm (cm³ 3 The ratio of (g-carbon support) (less than 5 nm / 5-70 nm pore volume ratio) was calculated.

[0142] Furthermore, the amount of adsorption at the point where the relative pressure P / P0 is 0.98 on the nitrogen adsorption isotherm at a temperature of 77K can be used to determine the total pore volume (cm³) of the metal-supported catalyst. 3 The specific surface area / g) was obtained. Then, using the analysis software attached to the specific surface area / pore distribution analyzer, the average pore diameter (nm) of the metal-supported catalyst was calculated using the following formula: Average pore diameter (nm) = 4 × {Total pore volume (cm³) 3 ( / g) × 10 21} / {specific surface area(m 2 ( / g) × 10 18}.

[0143] [Electrochemical Effective Surface Area (ECSA)] The electrochemical effective specific surface area (ECSA) (m²) of platinum contained in a metal-supported catalyst. 2 The concentration of Pt ( / g-Pt) was evaluated using the rotating ring disk electrode method with a rotating ring disk electrode device (RRDE-3A rotating ring disk electrode device ver.1.2, manufactured by BAS Corporation) and a dual electrochemical analyzer (CHI700C, manufactured by ALS Corporation).

[0144] Specifically, a triode rotating ring disk electrode device was first fabricated, having a working electrode containing a metal-supported catalyst. Specifically, a slurry was prepared by mixing 5 mg of the metal-supported catalyst with 50 μL of 5% Nafion® (Sigma-Aldrich, Nafion perfluorinated ion exchange resin, 5% solution (product number: 510211)), 400 μL of water, and 100 μL of isopropyl alcohol. Next, this slurry was subjected to sonication for 10 minutes, followed by homogenization for 2 minutes. The resulting slurry was then processed with a coating amount of metal-supported catalyst of 0.1 mg / cm².2 To achieve this, the metal-supported catalyst was applied to a working electrode (RRDE-3A ring-disk electrode, platinum ring-gold disk electrode, disk diameter 4 mm, manufactured by BAS Corporation) and dried to produce a working electrode on which the metal-supported catalyst was supported.

[0145] A platinum electrode (Pt counter electrode 23 cm, manufactured by BAS Corporation) was used as the counter electrode, and a reversible hydrogen electrode (RHE) (accumulation-type reversible hydrogen electrode, manufactured by EC Frontier Corporation) was used as the reference electrode. In this way, a rotating ring disk electrode apparatus was obtained having a working electrode containing a metal-supported catalyst, a platinum electrode as the counter electrode, and a reversible hydrogen electrode (RHE) as the reference electrode. A 0.1 M perchloric acid aqueous solution was used as the electrolyte.

[0146] Then, ECSA was measured using the above-described rotating ring disk electrode apparatus. Specifically, cyclic voltammetry (CV) was performed in a nitrogen atmosphere using a three-electrode rotating ring disk electrode apparatus having a working electrode containing a metal-supported catalyst.

[0147] In the CV (Voltage Control) experiment, nitrogen bubbling was first performed for 10 minutes to remove oxygen from the electrolyte. Then, the current density was recorded as a function of potential during a potential sweep at a sweep rate of 10 mV / sec in the potential range from 0.0 V (vs. NHE) to 0.94 V (vs. NHE).

[0148] From the cyclic voltammogram obtained in this way, ECSA(m 2 We obtained the amount of hydrogen adsorbed electricity (Q) from 0.0V (vs. NHE) to 0.4V (vs. NHE) during negative scanning in the cyclic voltammogram of the third cycle. Specifically, in the negative scanning, we obtained the amount of hydrogen adsorbed electricity (Q) from 0.0V (vs. NHE) to 0.4V (vs. NHE). Hupd )(mC / cm 2 From ) the area-converted electrical charge (210 μC / cm²) 2 ) and platinum coating amount (L Pt )(mg-Pt / cm 2 Using ), ECSA was obtained by the following equation (IV). JPEG2023129138000007.jpg17170

[0149] [Geometric specific surface area: powder X-ray diffraction method] Powder X-ray diffraction (XRD) was used to determine the geometric specific surface area (m²) of platinum contained in the metal-supported catalyst. 2 The concentration of Pt ( / g-Pt) was measured. Specifically, first, a sample of the powdered metal-supported catalyst was placed in a recess (2cm x 2cm x 0.5mm thick) of a glass sample plate and held down with a glass slide, ensuring that the sample was uniformly filled into the recess so that its surface coincided with the reference plane. Next, the glass sample plate was fixed to a wide-angle X-ray diffraction sample stage to prevent the shape of the filled sample from collapsing.

[0150] Powder X-ray diffraction measurements were then performed using an X-ray diffractometer (Rigaku RINT2100 / PC, Rigaku Corporation). The applied voltage and current to the X-ray tube were 50kV and 300mA, respectively. The sampling interval was 0.1°, the scanning speed was 1° / min, and the measurement angle range (2θ) was 5 to 90°. CuKα was used as the incident X-ray. The sample thickness was 0.5 mm, and the divergence slit width β was 2 / 3°.

[0151] The obtained XRD pattern was subjected to peak separation using a Gaussian function as described below, and the crystallite size corresponding to each peak obtained through peak separation was determined using Scherrer's formula. Then, for each peak, the value of "6 / density / crystallite size × peak area ratio × platinum atom ratio" was calculated, and by summing up these values ​​for all peaks, the geometric specific surface area of ​​platinum contained in the metal-supported catalyst was calculated.

[0152] For example, in the case of a metal-supported catalyst bearing catalyst metal particles containing platinum, the (111) diffraction line of platinum appears in the XRD pattern obtained by powder X-ray diffraction using CuKα rays at a diffraction angle (2θ) around 40° (for example, within the range of 35° to 44°). This diffraction line includes diffraction lines originating from pure platinum, diffraction lines originating from the platinum alloy, and diffraction lines originating from the carbon structure of the carbon support.

[0153] Diffraction lines originating from pure platinum are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 39.6° or greater and less than 39.8°. Diffraction lines originating from platinum alloys are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 39.9° or greater and less than 43.0°. Diffraction lines originating from the carbon structure of a carbon support are defined as diffraction lines with a peak top at a diffraction angle (2θ) of 43.3° or greater and less than 43.7°.

[0154] When a metal-supported catalyst contains multiple types of platinum alloys with different compositions and / or crystal structures, multiple diffraction lines originating from the platinum alloys will appear. The diffraction angle at which the peak top of the diffraction line originating from the platinum alloy is located is determined by its composition and crystal structure.

[0155] For example, composition Pt X Diffraction lines originating from platinum-cobalt alloys represented by Co(X=1~20) are defined as diffraction lines with a peak top at a diffraction angle between 39.9° and less than 41.8°. Composition: Pt X Diffraction lines originating from platinum-nickel alloys represented by Ni (X=1~20) are defined as diffraction lines with a peak top at a diffraction angle between 39.9° and 42.0°. Composition: Pt X Diffraction lines originating from a platinum-nickel-manganese alloy represented as Ni1Mn1(X=2~40) are defined as diffraction lines having a peak top at a diffraction angle between 39.9° and 41.2°.

[0156] Specifically, for example, diffraction lines originating from a platinum-cobalt alloy represented by the composition PtCo are defined as diffraction lines with a peak top at a diffraction angle of 41.1° or greater and less than 41.5°. Similarly, diffraction lines originating from a platinum-cobalt alloy represented by the composition Pt3Co are defined as diffraction lines with a peak top at a diffraction angle of 40.1° or greater and less than 40.5°. Furthermore, diffraction lines originating from a platinum-cobalt alloy represented by the composition Pt7Co are defined as diffraction lines with a peak top at a diffraction angle of 39.9° or greater and less than 40.1°.

[0157] Furthermore, for example, diffraction lines originating from a platinum-nickel alloy represented by the composition PtNi are defined as diffraction lines having a peak top at a diffraction angle of 41.6° or greater and less than 42.0°. Also, diffraction lines originating from a platinum-nickel alloy represented by the composition Pt3Ni are defined as diffraction lines having a peak top at a diffraction angle of 40.4° or greater and less than 41.2°. Also, diffraction lines originating from a platinum-nickel alloy represented by the composition Pt7Ni are defined as diffraction lines having a peak top at a diffraction angle of 39.9° or greater and less than 40.3°. Diffraction lines originating from a platinum-nickel-manganese alloy represented by the composition Pt6Ni1Mn1 are defined as diffraction lines having a peak top at a diffraction angle of 40.1° or greater and less than 40.8°.

[0158] Furthermore, when a metal-supported catalyst contains multiple types of platinum particles with the same composition and crystal structure but different crystallite sizes, multiple diffraction lines appear that have peak tops at approximately the same diffraction angle and have different full widths at half maximum.

[0159] In fact, in the XRD patterns obtained for the metal-supported catalyst, the (111) diffraction line of platinum appeared at a diffraction angle (2θ) of approximately 40°. Therefore, baseline correction was first performed. Specifically, a straight line connecting the diffraction intensity at a diffraction angle (2θ) of 30° and the diffraction intensity at 50° was determined as the baseline, and baseline correction was performed by subtracting this baseline from the intensity of each diffraction line.

[0160] Next, the baseline-corrected diffraction lines were separated into peaks originating from one or more types of pure Pt and / or one or more types of Pt alloys, and peaks originating from carbon. The separation of diffraction lines was performed by assuming that each of the multiple peaks obtained by the separation is represented by a Gaussian function, and optimizing the intensity of the Gaussian function of each of the multiple peaks, the diffraction angle of the peak top, and the full width at half maximum so that the sum of squared residuals obtained by summing the differences (residuals) between the intensity of the diffraction line and the sum of the intensities of each of the multiple peaks at each diffraction angle of the XRD figure for all diffraction angles is minimized.

[0161] Here, referring to the XRD pattern obtained by powder XRD measurement of the metal-supported catalyst in Example 1, we will explain the peak separation of the (111) diffraction line of platinum, which has a peak top at a diffraction angle (2θ) around 40° (within the range of 39° to 44°).

[0162] In the XRD pattern of the metal-supported catalyst in Example 1, after baseline correction, a diffraction line with a peak top appeared at a diffraction angle (2θ) around 40° (specifically, between 39.5° and 40.5°), as shown in Figure 2A. The shape of the middle part of this diffraction line was significantly narrower than the shape of the lower part. Therefore, it was considered that at least two diffraction lines overlapped at a diffraction angle (2θ) around 40°, including the diffraction line of a first platinum with a relatively large full width at half maximum and the diffraction line of a second platinum with a different crystallite size and a smaller full width at half maximum. Furthermore, since the metal-supported catalyst contains a carbon support, it was considered that a diffraction line originating from carbon was also included at a diffraction angle (2θ) around 43.5°.

[0163] Therefore, using the peak separation method described above, the diffraction line having a peak top at a diffraction angle (2θ) of approximately 40° was separated into three components: a peak originating from the first platinum, a peak originating from the second platinum, and a peak originating from carbon.

[0164] Figure 2A shows the results of peak separation into these three components. In Figure 2A, the "Baseline Corrected" diffraction line is the diffraction line obtained by applying baseline correction to the diffraction line obtained by XRD measurement, and the "Pt1" peak, the "Pt2" peak, and the "Carbon" peak are the first platinum-derived peak, the second platinum-derived peak, and the carbon-derived peak, respectively, obtained by peak separation of the "Baseline Corrected" diffraction line. The "Pt1+Pt2+Carbon" peak is the peak obtained by adding the "Pt1" peak, the "Pt2" peak, and the "Carbon" peak.

[0165] However, as shown in Figure 2A, when peak separation of the diffraction lines after baseline correction was performed so that the broadening of the tail from around 34° to 38° of the diffraction angle (2θ) matched the intensity of the peak top around 39.7°, the shoulders around 39° and 41° could not be reproduced.

[0166] In this regard, as mentioned above, the diffraction lines originating from pure platinum have their peak tops at a position between 39.6° and 39.8°, so it was considered that a third type of platinum diffraction line, with its peak top at around 39.7°, was also mixed in.

[0167] Therefore, the diffraction line with a diffraction angle (2θ) around 39.7° was separated into four components: a peak originating from the first platinum, a peak originating from the second platinum, a peak originating from the third platinum, and a peak originating from carbon.

[0168] Figure 2B shows the results of peak separation into these four components. In Figure 2B, the "baseline corrected" diffraction line is the diffraction line obtained by applying baseline correction to the diffraction line obtained by XRD measurement, and the "Pt1" peak, "Pt2" peak, "Pt3" peak, and "Carbon" peak are the first platinum-derived peak, the second platinum-derived peak, the third platinum-derived peak, and the carbon-derived peak, respectively, obtained by peak separation of the "baseline corrected" diffraction line.

[0169] Note that the peak obtained by summing the peaks of "Pt1", "Pt2", "Pt3", and "Carbon" almost perfectly matched the diffraction line "after baseline correction", and is therefore not shown in Figure 2B.

[0170] Thus, the sum of squared residuals when the peaks were separated into four components was reduced and became extremely small compared to the sum of squared residuals when the peaks were separated into three components. Therefore, it was concluded that the metal-supported catalyst in Example 1 is supported with first platinum particles, second platinum particles, and third platinum particles as Pt particles.

[0171] The crystallite sizes of the first, second, and third platinum particles were then calculated using Scherrer's equation: crystallite size (nm) = Kλ / βcosθ. Here, in Scherrer's equation, K is Scherrer's constant (0.94), λ is the wavelength of the CuKα line (0.15418 nm), β is the full width at half maximum (radians), and θ is the diffraction angle (radians).

[0172] Specifically, for example, the crystallite size of the first platinum particle was calculated by substituting the diffraction angle and full width at half maximum of the separation peak of "Pt1" in the XRD diagram shown in Figure 2B into Scherrer's formula. As a result, the crystallite size of the first platinum particle was 1.10 × 10⁻⁶. ―9 The calculation was found to be m, and the crystallite size of the second platinum particle is 3.52 × 10⁻¹⁰. ―9 The calculation was m, and the crystallite size of the third platinum particle was 15.3 × 10⁻¹⁰. ―9 It was calculated as m.

[0173] Furthermore, the peak area ratio of each of the three Pt-separated peaks obtained by the above-described peak separation (i.e., the peak area of ​​"Pt1", the peak area of ​​"Pt2", and the peak area of ​​"Pt3") was calculated by dividing each peak area by the sum of the areas of the three Pt-separated peaks. As a result, the peak area ratio of the first platinum particle was calculated to be 0.271, the peak area ratio of the second platinum particle was calculated to be 0.704, and the peak area ratio of the third platinum particle was calculated to be 0.025. The density of the platinum particles was 21.45 × 10⁻⁶. 6 g / m 3 The platinum atom ratio is 1.

[0174] Then, for each of these peaks, the value of "6 / density / crystallite diameter × peak area ratio × platinum atom ratio" was calculated, and by summing up the values ​​of all the peaks, the geometric specific surface area of ​​platinum contained in the catalyst metal particles was calculated. Specifically, the geometric specific surface area of ​​platinum contained in the catalyst metal particles supported on the metal-supported catalyst of Example 1 is 125.4(m²) by the following formula. 2The geometric specific surface area (m²) of platinum contained in the catalyst metal particles was calculated as follows: 2 / g-Pt)={6 / (21.45×10 6 ) / (1.10×10 ―9 ) × 0.271 × 1} + {6 / (21.45 × 10 6 ) / (3.52×10 ―9 ) × 0.704 × 1} + {6 / (21.45 × 10 6 ) / (15.30×10 ―9 ) × 0.025 × 1}.

[0175] Furthermore, Figure 3 shows the results of peak separation of diffraction peaks with a diffraction angle (2θ) around 40° (within the range of 39° to 44°) in the XRD pattern obtained for the metal-supported catalyst of Example 9. The peak separation for Example 9 will be explained below.

[0176] In the XRD pattern obtained from the powder XRD measurement of the metal-supported catalyst in Example 9, after baseline correction, a diffraction line with a peak top at a diffraction angle (2θ) of approximately 40.0° appeared. This diffraction line was thought to contain at least the diffraction line of the platinum-cobalt alloy Pt7Co. Therefore, it was separated into two components: a peak of the platinum-cobalt alloy Pt7Co and a peak derived from carbon.

[0177] However, optimizing the two components—the peak of the platinum-cobalt alloy Pt7Co and the peak derived from carbon—did not reproduce the shape of the peak top around a diffraction angle (2θ) of 40.0°. Therefore, it was considered that around a diffraction angle (2θ) of 40.0°, the diffraction line of the first platinum-cobalt alloy Pt7Co, which has a relatively large full width at half maximum, and the diffraction line of the second platinum-cobalt alloy Pt7Co, which has a different crystallite size and an even smaller full width at half maximum, were mixed together. Accordingly, the diffraction was separated into three components consisting of the peak of the first platinum-cobalt alloy Pt7Co, the peak of the second platinum-cobalt alloy Pt7Co, and the peak derived from carbon.

[0178] By optimizing the three components, the intensity of the peak top around a diffraction angle (2θ) of 40.0° could be reproduced, but the broadening of the tail of the diffraction line around a diffraction angle (2θ) of 34° to 38° could not be reproduced. Therefore, it was considered that the diffraction lines of pure platinum were also mixed in around a diffraction angle (2θ) of 34° to 38°. Accordingly, using the peak separation method described above, the diffraction line around a diffraction angle (2θ) of 40° was separated into four components consisting of a peak originating from the first platinum, a peak originating from the first platinum-cobalt alloy Pt7Co, a peak originating from the second platinum-cobalt alloy Pt7Co, and a peak originating from carbon.

[0179] As a result of separating the signal into four components, the sum of squared residuals was reduced to an extremely small value, and the peak obtained by summing the peaks of these four components almost perfectly matched the diffraction line after "baseline correction." Therefore, it was concluded that the metal-supported catalyst of Example 9 is supported with platinum particles and platinum-cobalt alloy particles, specifically the first platinum-cobalt alloy Pt7Co particles and the second platinum-cobalt alloy Pt7Co particles.

[0180] In Figure 3, the "baseline-corrected" diffraction line is the diffraction line obtained by applying baseline correction to the diffraction line obtained by XRD measurement. The "Pt1" peak, the "Pt7Co_1" peak, the "Pt7Co_2" peak, and the "Carbon" peak are the first platinum-derived peak, the first platinum-cobalt alloy Pt7Co-derived peak, the second platinum-cobalt alloy Pt7Co-derived peak, and the carbon-derived peak, respectively, obtained by peak separation of the "baseline-corrected" diffraction line.

[0181] The crystallite sizes of the first platinum particle, the first platinum-cobalt alloy Pt7Co particle, and the second platinum-cobalt alloy Pt7Co particle were calculated using Scherrer's formula described above. For example, the crystallite size of the first platinum particle was calculated by substituting the diffraction angle and full width at half maximum of the "Pt1" separation peak in the XRD diagram shown in Figure 3 into Scherrer's formula. As a result, the crystallite size of the first platinum particle was 1.26 × 10⁻⁶. ―9The calculation was found to be m, and the crystallite size of the first platinum-cobalt alloy Pt7Co particle is 3.15 × 10⁻¹⁵. ―9 The calculation was found to be m, and the crystallite size of the second platinum-cobalt alloy Pt7Co grain is 9.10 × 10 ―9 It was calculated as m.

[0182] Furthermore, the peak area ratio of each of the three separated peaks obtained by the above-described peak separation (i.e., the peak area of ​​"Pt1", the peak area of ​​"Pt7Co_1", and the peak area of ​​"Pt7Co_2") was calculated by dividing each peak area by the sum of the areas of the three separated peaks. As a result, the peak area ratio of the first platinum particle was calculated to be 0.340, the peak area ratio of the first platinum-cobalt alloy Pt7Co was calculated to be 0.508, and the peak area ratio of the second platinum-cobalt alloy Pt7Co was calculated to be 0.152. The density of the platinum particles was 21.45 × 10⁻⁶. 6 g / m 3 The platinum atom ratio is 1, and the density of platinum-cobalt alloy Pt7Co particles is 19.88 × 10⁻¹⁶. 6 g / m 3 The platinum atom ratio is 0.875.

[0183] Then, for each of these peaks, the value "6 / density / crystallite diameter × peak area ratio × platinum atom ratio" was calculated, and by summing up the values ​​of all the peaks, the geometric specific surface area of ​​platinum contained in the catalyst metal particles was calculated. Specifically, the geometric specific surface area of ​​platinum contained in the catalyst metal particles supported on the metal-supported catalyst of Example 9 is 122.5 m², calculated using the following formula. 2 The geometric specific surface area (m²) of platinum contained in the catalyst metal particles was calculated as / g-Pt: 2 / g-Pt)={6 / (21.45×10 6 ) / (1.26×10 ―9 ) × 0.340 × 1} + {6 / (19.88 × 10 6 ) / (3.15×10 ―9 ) × 0.508 × 0.875} + {6 / (19.88 × 10 6 ) / (9.10×10 ―9 ) × 0.152 × 0.875}.

[0184] [Carbon anchoring ratio] For each metal-supported catalyst, the platinum ECSA (m) obtained as described above was obtained. 2 ( / g-Pt), and the geometric specific surface area (m²) of platinum obtained as described above. 2 The carbon anchoring ratio (%) was calculated by using ( / g - Pt) as the "electrochemical effective specific surface area" and "geometric specific surface area" in the following formula (I), respectively. That is, the carbon anchoring ratio (%) is calculated as the ECSA (m) of platinum. 2 ( / g - Pt) is the geometric specific surface area (m²) of platinum. 2 The value obtained by dividing by (g - Pt) was subtracted from 1, and the resulting value was multiplied by 100 to calculate the result. JPEG2023129138000008.jpg21170

[0185] [Carbon anchoring amount] For each metal-supported catalyst, the platinum content (weight %) and the geometric specific surface area (m²) of platinum obtained as described above were determined. 2 / g-Pt), and platinum ECSA (m 2 The carbon anchoring amount was calculated using the following formula (II) as the "precious metal content (weight %)", "geometric specific surface area", and "electrochemical effective specific surface area", respectively, with the value of (g - Pt) being used. That is, the carbon anchoring amount (m 2 The value obtained by dividing the platinum content (weight %) by 100 is multiplied by the geometric specific surface area (m²) of platinum. 2 / g-Pt) and platinum ESCA(m 2 It was calculated by multiplying by the difference between ( / g - Pt). JPEG2023129138000009.jpg28170

[0186] [Durability Index] For each metal-supported catalyst, the carbon anchoring ratio (%) obtained as described above and the Raman D half-width (cm) obtained as described above are given. -1 Using the following formula (III), the durability index was calculated. JPEG2023129138000010.jpg21170

[0187] [Performance evaluation of batteries having electrodes containing metal-supported catalysts] The performance of a fuel cell having a cathode containing a metal-supported catalyst was evaluated. Specifically, a battery cathode with a catalyst layer containing a metal-supported catalyst was first manufactured. That is, 0.25 g of metal-supported catalyst was added to an amount of electrolyte (equivalent mass EW = 820) with a weight ratio of 1.1 to the carbon support, and then 2 g each of distilled water and 1-propanol were added to prepare an electrolyte solution. This electrolyte solution and 25 g of balls were placed in a pot and mixed in a ball mill at 200 rpm for 50 minutes to obtain a slurry-like catalyst layer composition containing the metal-supported catalyst, which was uniformly dispersed.

[0188] The obtained slurry-like catalyst layer composition was spread over an area of ​​5 cm² on a gas diffusion layer ("29BC", manufactured by SGL Carbon) (2.3 cm × 2.3 cm). 2 In this region, the platinum content per unit area of ​​the battery electrode is 0.2 (mg-Pt / cm²). 2 A catalyst layer was formed on the gas diffusion layer by applying it in such a manner and drying it. In this way, a battery electrode was obtained in which a catalyst layer containing a metal-supported catalyst was formed.

[0189] Next, a fuel cell was manufactured that included a battery electrode having a catalyst layer containing a metal-supported catalyst. Specifically, the battery electrode containing the catalyst layer (positive electrode catalyst layer) manufactured as described above was used as the positive electrode.

[0190] On the other hand, the negative electrode was prepared as follows: 0.5 g of Pt / C (a catalyst containing platinum particles supported on a carbon support: UNPC40-II, manufactured by Ishifuku Metal Industries Co., Ltd.), 10 g of 5% Nafion®, 2 g of distilled water, and 25 g of balls were placed in a pot and mixed in a ball mill at 200 rpm for 50 minutes to prepare a slurry-like Pt / C composition. This slurry-like Pt / C composition was then subjected to a gas diffusion layer (5 cm 2 ) The platinum content per unit area is 0.1 (mg-Pt / cm²) 2A negative electrode was fabricated in the same manner as the positive electrode described above, except that the condition was met, and the negative electrode included a catalyst layer (negative electrode catalyst layer) formed from the Pt / C composition.

[0191] Then, a solid polymer electrolyte membrane (Dupont, "NAFION® 211") was placed between the positive electrode catalyst layer and the negative electrode catalyst layer, and these were pressed together for 3 minutes at 150°C and 1 MPa to produce a MEA. A pair of gaskets were attached to this MEA, and then sandwiched between a pair of separators to produce a fuel cell single cell. Subsequently, the single cell produced as described above was installed in a fuel cell automatic evaluation system (Toyo Technica Co., Ltd.), and a power generation test was first performed, followed by a durability test.

[0192] The power generation test involved supplying saturated humidified air (oxygen) at a back pressure of 150 kPa to the positive electrode side at a rate of 2.5 L / min (relative humidity 100%), and saturated humidified hydrogen at a rate of 1.0 L / min (relative humidity 100%) to the negative electrode side. The cell temperature was set to 75°C, and the open-circuit voltage was measured for 5 minutes. Subsequently, the cell current density was measured at 4.0 A / cm². 2 From 0 A / cm 2 The cell voltage was measured after holding each current density for 3 minutes.

[0193] Furthermore, the output characteristics include a current density of 2.5 A / cm². 2 The voltage (mV) was measured at [location]. Furthermore, the catalytic activity was measured at a current density of 0.2 A / cm². 2 The voltage (mV) was measured at [location]. Additionally, the voltage at the start of the durability test was set to a current density of 1.0 A / cm². 2 The voltage (mV) at [location] was recorded.

[0194] Next, a durability test was conducted. Specifically, the cell temperature was set to 70°C, saturated humidified nitrogen was supplied to both sides of the single cell at a back pressure of 35kPa at a rate of 0.5L / min (relative humidity 100%), saturated humidified hydrogen was supplied to the anode side at a rate of 0.5mL / min (relative humidity 100%), and the durability test was performed by repeating a square wave cycle in which the potential was held at 0.6V for 10 seconds and then at 1.2V for 3 seconds.

[0195] After performing the cycle of the rectangular wave 10,000 times, a power generation test was conducted again, and the voltage (mV) at a current density of 1.0 A / cm after the durability test was recorded. Then, from the voltage (mV) measured as the initial performance in the power generation test before the durability test at 1.0 A / cm 2 the voltage loss (mV), which is the value obtained by subtracting the voltage (mV) at 1.0 A / cm 2 measured in the power generation test after the durability test from the voltage (mV) at 1.0 A / cm 2 measured in the power generation test after the durability test (voltage (mV) after 10,000 cycles), was used as an index of durability in the durability test.

[0196] [Results] Figure 4A shows the manufacturing conditions of the metal-supported catalysts of Examples 1 to 9 and Examples C1 to C7, and the results of evaluating the characteristics of the fuel cells including the metal-supported catalysts.

[0197] In the durability test, as described above, the durability test was conducted at potentials of 0.6 V and 1.2 V. In an environment where the potential is relatively high at about 1.2 V, deterioration due to oxidation of the catalyst metal particles and / or the carbon support tends to progress. On the other hand, in an environment where the potential is relatively low at about 0.6 V, deterioration (for example, aggregation and / or dissolution of the catalyst metal particles supported on the carbon support) tends to progress when the once-oxidized catalyst metal particles and / or the carbon support are reduced. Therefore, the smaller the voltage loss in the durability test, the higher the durability of the carbon support and the catalyst metal particles contained in the metal-supported catalyst.

[0198] In this regard, according to the voltage loss in the durability test shown in Figure 4A, the durability of the metal-supported catalysts of Examples 1 to 9 was superior to that of Examples C1, C3, and C5, and was comparable to that of Example C2. Also, the durability of the metal-supported catalysts of Examples 1, 3 to 5, and 8 was superior to that of Examples 2, 6, 7, and 9, and the durability of the metal-supported catalysts of Examples 3 and 8 was superior to that of Examples 1, 4, and 5. Note that the metal-supported catalysts of Examples C4, C6, and C7 showed significant deterioration in the durability test and were difficult to measure.

[0199] The current density of 2.5 A / cm showing the output characteristics of the metal-supported catalyst2 A higher voltage (mV) indicates that the output characteristics of the metal-supported catalyst are superior. Specifically, 2.0 A / cm² is a good value. 2 In the high current density region described above, a large amount of water is generated, which fills the pores of the carbon support, hindering mass transport and resulting in a decrease in the battery's voltage performance.

[0200] In this regard, according to Figure 4A, the power characteristics of the metal-supported catalysts in Examples 1-9 were superior to those of Examples C2, C3, and C5-C7, and comparable to those of Examples C1 and C4. Furthermore, the power characteristics of Examples 1-7 and 9 were superior to those of Example 8, and the power characteristics of Example 9 were superior to those of Examples 1-7.

[0201] Current density of 0.2 A / cm² indicates catalytic activity of the metal-supported catalyst. 2 The voltage (mV) in this region indicates that a higher value indicates better catalytic activity of the metal-supported catalyst. In other words, the overpotential of a fuel cell is classified into activation overpotential, resistance overpotential, and diffusion overpotential, but in the low current density region of 0.2 A / cm² 2 Therefore, because the effects of resistive overpotential and diffusion overpotential are small, it is suitable for evaluating catalytic activity.

[0202] In this regard, according to Figure 4A, the catalytic activity of the metal-supported catalysts in Examples 1-9 was superior to that of Examples C2, C5, and C6, and comparable to that of Examples C1, C3, C4, and C7. Furthermore, the catalytic activity of Examples 1-7 and 9 was superior to that of Example 8, and the catalytic activity of Example 9 was superior to that of Examples 1-7.

[0203] Figure 4B shows the results of evaluating the properties of the metal-supported catalysts in each example. Regarding the Raman D half-width (FHA) of the metal-supported catalysts in Examples 1-9, it was larger than that of Examples C2 and C5, similar to that of Examples C1 and C3, and smaller than that of Examples C4, C6, and C7. Furthermore, the metal-supported catalysts in Examples 2-9 had a smaller Raman D FHA than that of Example 1, and the metal-supported catalysts in Examples 3-9 had a smaller Raman D FHA than that of Example 2.

[0204] Regarding the BET specific surface area, the metal-supported catalysts of Examples 1-9 had a larger BET specific surface area than those of Examples C2 and C5-C7, similar to those of Examples C3 and C4, and smaller than that of Example C1. Furthermore, the metal-supported catalysts of Examples 1-4 and 7-9 had a larger BET specific surface area than those of Examples 5 and 6, and the metal-supported catalysts of Examples 1-3 and 9 had a larger BET specific surface area than those of Examples 4, 7, and 8.

[0205] Regarding the average pore size, the metal-supported catalysts of Examples 1-9 had an average pore size similar to that of Examples C1, C3, C4, and C7, and smaller than that of Examples C2, C5, and C6. Furthermore, the metal-supported catalysts of Examples 1-5 and 7-9 had an average pore size smaller than that of Example 6, and the metal-supported catalysts of Examples 1-3 and 9 had an average pore size smaller than that of Examples 4, 5, 7, and 9.

[0206] Regarding the pore volume ratio of less than 5 nm / 5-70 nm, the metal-supported catalysts of Examples 1-9 had a pore volume ratio of less than 5 nm / 5-70 nm that was greater than that of Examples C2, C4, and C5, and similar to that of Examples C1, C3, C6, and C7. Furthermore, the metal-supported catalysts of Examples 1-5 and 7-9 had a pore volume ratio of less than 5 nm / 5-70 nm that was greater than that of Example 6, the metal-supported catalysts of Examples 1-4 and 7-9 had a pore volume ratio of less than 5 nm / 5-70 nm that was greater than that of Example 5, and the metal-supported catalysts of Examples 1-3 and 9 had a pore volume ratio of less than 5 nm / 5-70 nm that was greater than that of Examples 4, 7, and 8.

[0207] Regarding the platinum content, the metal-supported catalysts in Examples 1-9 had a platinum content similar to that of Examples C1-C7. Furthermore, the metal-supported catalysts in Examples 1-8 had a higher platinum content than that of Example 9.

[0208] Regarding the ECSA of platinum, the metal-supported catalysts in Examples 1-9 had a platinum ECSA that was greater than that of Examples C2-C5, similar to that of Example C8, and smaller than that of Examples C1 and C7. Furthermore, the metal-supported catalysts in Examples 1-4, 6, 7, and 9 had a larger ECSA than that of Examples 5 and 8, and the metal-supported catalysts in Examples 2-4, 7, and 9 had a larger ECSA than that of Examples 1 and 6.

[0209] Regarding the geometric specific surface area of ​​platinum, the metal-supported catalysts in Examples 1-9 had a larger specific surface area than those in Examples C2, C3, and C5, was comparable to that of Example C4, and was smaller than that of Examples C1, C6, and C7. Furthermore, the metal-supported catalysts in Examples 1-4, 6, 7, and 9 had a larger specific surface area of ​​platinum than those in Examples 5 and 8, and the metal-supported catalysts in Examples 1-4, 7, and 9 had a larger specific surface area of ​​platinum than that of Example 6.

[0210] Regarding the carbon anchoring ratio, the metal-supported catalysts in Examples 1-9 had a higher carbon anchoring ratio than those in Examples C1-C3 and C5, and a lower carbon anchoring ratio than those in Examples C4, C6, and C7. Furthermore, the metal-supported catalysts in Examples 1-6, 8, and 9 had a higher carbon anchoring ratio than that of Example 7, and the metal-supported catalysts in Examples 1, 3, and 9 had a higher carbon anchoring ratio than those in Examples 2, 4, 5, and 8. In addition, the metal-supported catalysts in Examples 3 and 9 had a lower carbon anchoring ratio than that of Example 1.

[0211] Regarding carbon anchoring, the metal-supported catalysts in Examples 1-9 had a higher carbon anchoring amount than those in Examples C1-C3 and C5, similar to that of Example C4, and lower than that of Examples C6 and C7. Furthermore, the metal-supported catalysts in Examples 1-4, 6, and 9 had a higher carbon anchoring amount than those in Examples 5, 7, and 8, and the metal-supported catalysts in Examples 1-3 and 9 had a higher carbon anchoring amount than those in Examples 4 and 6. In addition, the metal-supported catalysts in Examples 2, 3, and 9 had a lower carbon anchoring ratio than that of Example 1.

[0212] Regarding the durability index, the metal-supported catalysts in Examples 1-9 had a higher durability index than those in Examples C1, C3, C6, and C7, and a similar durability index to that of Examples C2, C4, and C5. Furthermore, the metal-supported catalysts in Examples 1, 3-6, 8, and 9 had a higher durability index than those in Examples 2 and 7, the metal-supported catalysts in Examples 3-6, 8, and 9 had a higher durability index than those in Example 1, and the metal-supported catalysts in Examples 3 and 9 had a higher durability index than those in Examples 4-6 and 8.

Claims

1. A carbon support; catalytic metal particles, which contain a precious metal and are supported on the carbon support; A metal supported catalyst comprising: The Raman spectrum obtained by Raman spectroscopy shows a Raman shift of 1340 cm -1 The half-width at half maximum of the D band having a peak top in the vicinity of 50.0 cm -1 is as follows: The carbon anchoring ratio calculated by the following formula (I) is 15.0% or more. (In the above formula (I), the "electrochemically effective specific surface area" and the "geometric specific surface area" respectively refer to the electrochemically effective specific surface area (m2) of the precious metal contained in the metal-supported catalyst, which is obtained by cyclic voltammetry of potential sweep at a sweep rate of 10 mV / sec using a rotating ring-disk electrode apparatus having a working electrode on which the metal-supported catalyst is supported. 2 / g-noble metal), and the geometric specific surface area (m2) of the precious metal contained in the metal-supported catalyst, which is obtained by performing peak separation of the (111) diffraction line of the precious metal appearing in the X-ray diffraction pattern obtained by powder X-ray diffraction of the metal-supported catalyst, calculating the value of "6 / density / crystallite size x peak area ratio x precious metal atom ratio" for each peak obtained by the peak separation, and adding up the calculated values ​​for all the peaks. 2 / g-precious metals). Metal supported catalysts.

2. The average pore diameter is 8.0 nm or less. The metal supported catalyst of claim 1.

3. The volume (cm) of pores with a diameter of 5 nm or more and 70 nm or less 3 / g-carbon support) vs. the volume of pores with a diameter of less than 5 nm (cm 3 / g-carbon support) is 1.5 or more; The metal supported catalyst according to claim 1 or 2.

4. BET specific surface area is 350 (m 2 / g-carbon support) or more; The metal supported catalyst according to any one of claims 1 to 3.

5. The ratio of the weight of the precious metal to the weight of the metal-supported catalyst is 30% by weight or more. The metal supported catalyst according to any one of claims 1 to 4.

6. The electrochemically effective specific surface area of ​​the precious metal contained in the metal-supported catalyst is 45 (m 2 / g-precious metal) or more; The metal supported catalyst according to any one of claims 1 to 5.

7. The geometric specific surface area of ​​the precious metal contained in the metal-supported catalyst is 52 (m 2 / g-precious metal) or more; The metal supported catalyst according to any one of claims 1 to 6.

8. The carbon anchoring amount calculated by the following formula (II) is 5.0 m 2 / g or more; (In the above formula (II), the "precious metal content (wt%)" is the ratio of the weight of the precious metal to the weight of the metal-supported catalyst, and the "geometric specific surface area" and the "electrochemically effective specific surface area" are the geometric specific surface areas (m 2 / g-precious metal) and electrochemically effective specific surface area (m 2 / g-precious metals). The metal supported catalyst according to any one of claims 1 to 7.

9. The durability index calculated by the following formula (III) is 0.50 cm or more. (In the above formula (III), the "carbon anchoring ratio (%)" is calculated by the above formula (I), and the "Raman D half-width at half maximum" is the half-width at half maximum of the D band (cm -1 ) The metal supported catalyst according to any one of claims 1 to 8.

10. The metal-supported catalyst according to any one of claims 1 to 9, electrode.

11. Comprising the electrode of claim 10 battery.